Pemberdayaan Petani Dalam Pengendalian Hama Tikus Melalui Metode Kimiawi di Desa Pertapan Maduretno - Pahan, Mephalti Ozerli; Bramasari, Nadya Ayu; Amelia, Vioni Putri; Roidah, Ida Syamsu (CV Litera Inti Aksara, 2025)
Rice farming in Indonesia faces a serious threat from rodent pests, particularly the rice field rat (Rattus argentiventer), which can significantly reduce crop yields. This study aims to empower farmers in controlling rat infestations through chemical methods in Pertapan Maduretno Village, Sidoarjo. The activities were carried out in three phases: preparation, implementation, and evaluation. The method involved providing bait made from unhusked rice mixed with Klerat rodenticide (containing 0.005% brodifacoum), which was distributed in areas frequently traversed by rats. The results indicated that this method effectively suppressed the pest population, as the poison works systemically, even affecting the offspring. However, long-term use poses the risk of developing resistance in rats and endangering non-target animals. Therefore, chemical control should be accompanied by regular monitoring and can be integrated with natural methods, such as utilizing barn owls as predators. This integrated approach supports more sustainable and environmentally friendly pest management.